Attractiveness, acceptability, and value of orthodontic appliances - Rosvall, Michael D.; Fields, Henry W.; Ziuchkovski, James; Rosenstiel, Stephen F.; Johnston, William M. (American journal of orthodontics and dentofacial orthopedics, 2009)
The aim of this study was to quantify laypersons' assessments of attractiveness, acceptability, and value of orthodontic appliances. Orthodontic appliances were placed in a consenting adult, and digital images were captured, standardized, and incorporated into a computer-based survey. The survey displayed various images of orthodontic appliances for rating by a sample of adults (n=50). Subjects rated each image for (1) attractiveness on a visual analog scale, (2) acceptability of placement of each appliance on themselves and their children, and (3) willingness to pay for each appliance for an adult or a child relative to a metal appliance standard. Rater reliability for the attractiveness, acceptability, and value ratings was assessed by rating 3 images twice. Overall reliability values for attractiveness were intraclass correlation coefficient=0.87 and κ=0.81 for acceptability and κ=0.88 for value ratings. The raters' annual income was not significant for attractiveness, acceptability, or value ratings. No significant difference was found between parent and child ratings for either the appliance acceptability or value ratings. Appliance brand, material, and wire were significant factors affecting attractiveness and value ratings. Attractiveness ratings were grouped in the following hierarchy of appliance types: alternative appliances such as clear trays and simulated lingual appliances > ceramic appliances > ceramic self-ligation appliances > all hybrid and stainless steel appliances. Acceptability ratings for all alternative and ceramic appliances were statistically equivalent, and statistically higher than those for other appliances. Standard metal braces had the lowest acceptability rate of 55%. The willingness-to-pay value of appliances relative to a metal standard appliance ranged from $629 for lingual appliances to $167 for a hybrid self-ligation appliance. These findings show that a significant number of patients find commonly used appliances unattractive and unacceptable. Patients are willing to pay more money for appliances they deem more esthetic.